FIKIH INTERAKSI MEDIA SOSIAL: ANALISIS KITAB KUNING DALAM PEMBELAJARAN SANTRI DI ERA DIGITAL - M. Sani Hafiz Rusydi; Riki Naldi Hasibuan; Afif Imran Prasetyo; M. Getsy Terrano (JIP: Jurnal Ilmu Pendidikan, 2025)
The digital era has brought significant changes in the way humans interact, including among students in Islamic boarding schools. Social media has become a new space that challenges the ethical values of Islam taught in the yellow book. This article aims to analyze how the principles of fiqh in the yellow book can be used as a reference in shaping the ethics of students in social media. The method used is qualitative-descriptive based on literature studies of classical books such as Ta'limul Muta'allim, Bidayatul Hidayah, and Ihya Ulumuddin, and is strengthened by the views of contemporary scholars and fatwas of authoritative institutions. The results show that values such as tabayyun, husnuzhan, ghibah prohibition, and communication manners have strong relevance to the current social media dynamics. The integration of the yellow book into digital ethics learning in pesantren is a solution to form the character of students who are wise in interacting online.